2017
DOI: 10.1346/ccmn.2017.064065
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Studies of the Clay Minerals Society Source Clay Montmorillonite STx-1b

Abstract: For more than forty years, The Clay Minerals Society has dispensed a set of source clays which have enabled a large number of researchers to work on similar materials. Many of these source clays remained unchanged over the years but, conversely, other clays have gone out of stock and thus were replaced. This was the fate of montmorillonite STx-1a, which was replaced by STx-1b. Although STx-1a and STx-1b share many basic chemical and mineralogical features, some minor differences exist that can affect behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Montmorillonite STx-1b (Mt) from Gonzales County (Texas, USA) was obtained from the Clay Minerals Society, chemical formula: [4] (Si 7.753 Al 0.247 ) [6] (Al 3.281 Mg 0.558 Fe 0.136 Ti 0.024 Mn 0.002 ) [12] (Ca 0.341 Na 0.039 K 0.061 ) O 20 (OH) 4 , cation exchange capacity (CEC): 66.1 (±2.1) meq/100 g (Castellini et al, 2017). 1,10-phenanthroline monohydrate (Phen) and anhydrous NH 3 (>99 analytical grade purity) were purchased from Sigma Aldrich, CuSO 4 •5H 2 O (>99% analytical grade purity) from Carlo Erba.…”
Section: Methodsmentioning
confidence: 99%
“…Montmorillonite STx-1b (Mt) from Gonzales County (Texas, USA) was obtained from the Clay Minerals Society, chemical formula: [4] (Si 7.753 Al 0.247 ) [6] (Al 3.281 Mg 0.558 Fe 0.136 Ti 0.024 Mn 0.002 ) [12] (Ca 0.341 Na 0.039 K 0.061 ) O 20 (OH) 4 , cation exchange capacity (CEC): 66.1 (±2.1) meq/100 g (Castellini et al, 2017). 1,10-phenanthroline monohydrate (Phen) and anhydrous NH 3 (>99 analytical grade purity) were purchased from Sigma Aldrich, CuSO 4 •5H 2 O (>99% analytical grade purity) from Carlo Erba.…”
Section: Methodsmentioning
confidence: 99%
“…The UV-Vis spectra of Fe 3+ phen in solution, obtained at different concentrations, were reported by Bernini et al [20][21][22]. Fe charge-transfer transition) at λ = 356 nm and two additional bands at 223 and 266 nm attributable to the aromatic ligand.…”
Section: Dr Uv-vis Measurementsmentioning
confidence: 55%
“…Some previous studies dealing with the intercalation of lamellar layered silicates, such as montmorillonite, with cationic metal complexes, specifically Fe 3+ phenanthroline, showed that modifications by ion exchange reactions provide larger spacing between layers [20,21]. In these layer silicates, Fe…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Montmorillonite is a natural nanomineral (layer thickness~1.0 nm) belonging to the smectite group. The intrinsic montmorillonite properties such as low permeability, high surface area, and cation exchange capacity (CEC) [11] promote its application in such context.…”
Section: Introductionmentioning
confidence: 99%